Answer:
<h2>VX = 26</h2>
Step-by-step explanation:
If W is the midpoint of VX then VW = WX. Therefore we have the equation:
2x + 5 = 4x - 3 <em>subtract 5 from both sides</em>
2x = 4x - 8 <em>subtract 4x from both sides</em>
-2x = -8 <em>divide both sides by (-2)</em>
x = 4
VX = VW + WX
VX = 2x + 5 + 4x - 3 = (2x + 4x) + (5 - 3) = 6x + 2
Put the value of x = 4 to 6x + 2:
VX = 6(4) + 2 = 24 + 2 = 26
Subtract original amount from new amount:
84 - 39 = 45
He bought 45 books.
Answer:Factor by grouping.
Tap for more steps...
(
x
−
4
)
(
3
x
+
1
)
x
−
4
Reduce the expression by cancelling the common factors.
Tap for more steps...
3
x
+
1
Step-by-step explanation:
Let's form the difference of the two expressions and see what we can learn.
(2y -x) -(2x -y) = 2y -x -2x +y = 3y -3x = 3(y -x)
Since y > x, this is positive, so 2y -x is greater than 2x -y.